Types of Figurative Language Found in English Slogan Beverage Products - Eldis, Plasidiana; Komang Dian Puspita Candra; Ida Bagus Gde Nova Winarta (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study aims to identify and analyze the types figurative language found in English Slogan beverage advertisements, especially about the types and meanings of figurative language that contained in English Slogan. The problem discussed in this study are (1) what types of figurative language found in English Slogan of beverage advertisements, and (2) how the meaning of the figurative language that contained in English sloganof beverage advertisements. Thus, in analyzes the data the researcher used the descriptive qualitative method by using theory proposed by Kennedy (1983) and Leech (1981). As the result of this analysis the researcher found that are 4 types of figurative language in English slogan of beverage advertisements. They are: comparative 14 data or 48,28%, contradictive 9 data or 31,03%, and correlative 6 data or 20,69%. Comparative figurative language consists of Personification, Metaphor and Simile. Contradictive figurative language consists of Hyperbole, Litotes, Paradox and Irony. Correlative language consists of Metonymy, Synechdoche, Symbol, Allusion and Elipsis. For the meaning of the figurative language contained in English slogan of beverage advertisements the researcher found 2 types of meaning, such as; conceptual meaning 1 data or 20% and the connotative meaning 4 data or 80%. Keywords: Figurative Language, English slogan, Products .